Role of stem cells in tooth bioengineering - Kamleshwar Singh; Niraj Mishra; Lakshya Kumar; Kaushal Kishore Agarwal; Bhaskar Agarwal (Journal of Oral Biology and Craniofacial Research)
ABSTRACT: The creation of teeth in the laboratory depends upon the manipulation of stem cells and requires a synergy of all cellular and molecular events that finally lead to the formation of tooth-specific hard tissues, dentin, and enamel. This review focuses on the different sources of stem cells that have been used for making teeth in vitro. The search was performed from 1970 to 2012 and was limited to English language papers. The keywords searched on medline were ‘stem cells and dentistry,’ ‘stem cells and odontoblast,’ ‘stem cells and dentin,’ and ‘stem cells and ameloblasts.’